Peningkatan Hasil Belajar PAI Menggunakan Model Make a Match di SDN 04 Setia - Saadah, Ummi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes in Islamic Religious Education and Character Education in Grade V of SD Negeri 04 Setia through the application of the Make a Match learning model. The research background reveals low student performance in this subject, caused by conventional teaching methods like lectures that tend to be monotonous and fail to engage students actively. This research was conducted in the second semester of the 2024/2025 academic year, focusing on the topic "Living Peacefully in Harmony." The Make a Match learning model was chosen for its ability to enhance student interaction, motivation, and critical thinking skills through enjoyable and interactive learning activities. Data were collected through cognitive domain learning outcome tests. The study results showed that implementing the Make a Match learning model significantly improved students’ learning outcomes in Islamic Religious Education and Character Education in Grade V of SD Negeri 04 Setia.